Cover Feature: Self‐Immolation of a Bacterial Dehydratase Enzyme by its Epoxide Product (Chem. Eur. J. 36/2020). Issue 36 (9th June 2020) - Lence, Emilio; Maneiro, María; Sanz‐Gaitero, Marta; van Raaij, Mark J.; Thompson, Paul; Hawkins, Alastair R.; González‐Bello, Concepción
Abstract : Enzyme self‐immolation : The cover shows how the type I dehydroquinase enzyme catalyzes its self‐destruction by transforming an unreactive 2‐hydroxyethylammonium derivative into an epoxide that triggers the covalent modification of the catalytic lysine residue. This process is responsible of the in vitro anti‐virulence activity of the ligand. More information can be found in the Full Paper by C. González‐Bello, et al. on page 8035 .